Determinants of the decision to enroll in community-based health insurance among households in the West Guji Zone, Oromia State, southern Ethiopia, in 2022 - Gelgelo Wodessa; Miesa Gelchu; Anteneh Fikrie; Gemechis Tuke (Frontiers in Health Services)
BackgroundIn recent years, the Ethiopian government has introduced community-based health insurance (CBHI) schemes to increase healthcare accessibility and affordability. Despite these efforts, enrolment rates remain low, posing challenges to achieving universal health coverage. This study investigates the determinants influencing household enrolment decisions in community-based health insurance within the West Guji Zone, Oromia Regional State, southern Ethiopia, in 2022.Methods and materialsA community-based, unmatched case-control study was conducted among 690 randomly selected households (345 cases and 345 controls) in the West Guji Zone from 15 April to 15 June 2022. Data were collected via a pretested and structured face-to-face interviewer-administered questionnaire. The data were entered into EpiData 3.1 and analyzed via SPSS Version 26. Bivariate and multivariate binary logistic regression models were used to identify the determinants of enrolment decisions in community-based health insurance. An adjusted odds ratio (AOR) with a 95% confidence interval and p-value <0.05 was used to declare statistically significant associations.ResultsThe findings of this study revealed that factors such as no formal education (AOR = 2.885, 95% CI: 1.252, 6.648), negative perception (AOR = 0.067, 95% CI: 0.040, 0.112), poor and middle wealth index (AOR = 0.307, 95% CI: 0.166, 0.569), community solidarity practices (AOR = 4.266, 95% CI: 2.352, 7.736), trust in the CBHI scheme (AOR = 4.782, 95% CI: 2.926, 7.816), quality of service (AOR = 2.209, 95% CI: 1.324, 3.687), availability of prescribed drugs (AOR = 1.829, 95% CI: 1.102, 3.035), and satisfaction with services (AOR = 3.209, 95% CI: 1.937, 5.315) were identified as significant determinants of CBHI enrolment decisions.ConclusionThis study revealed that a lack of formal education, negative perceptions, and a lower wealth index negatively impact CBHI enrolment. However, community solidarity practices, trust, quality of service, availability of prescribed drugs, and satisfaction positively influence CBHI enrolment. This study highlights the need for targeted interventions to increase community awareness, foster community solidarity at the local level, increase trust in the health system, and increase the affordability of premiums, thereby promoting community-based health insurance enrolment and achieving universal health coverage in Ethiopia.